2021
DOI: 10.30958/aje.8-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Teachers’ Pedagogical Content Knowledge Involving the Relationships between Perimeter and Area

Abstract: This study aims to investigate and compare mathematics teachers’ knowledge of pedagogical content, knowledge of students’ understanding and knowledge of instructional strategies, subcomponents of pedagogical content knowledge, student errors in the relationship between perimeter and areas in rectangles, squares, and parallelograms. 10 pre-secondary school in-service mathematics teachers and 10 prospective mathematics teachers participated in the study. The qualitative case research approach was used. To collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…When compared to novice teachers, experienced teachers are more likely to use more instructional approaches in response to student performance cues (Ekmekci et al, 2019). Furthermore, according to the findings, prospective teachers have fewer PCK than inservice teachers (Yilmaz & Demir, 2021). It has been believed that the lack of prospective teachers' experiences or subject matter knowledge leads to this phenomenon.…”
Section: Teaching Experiencementioning
confidence: 94%
See 2 more Smart Citations
“…When compared to novice teachers, experienced teachers are more likely to use more instructional approaches in response to student performance cues (Ekmekci et al, 2019). Furthermore, according to the findings, prospective teachers have fewer PCK than inservice teachers (Yilmaz & Demir, 2021). It has been believed that the lack of prospective teachers' experiences or subject matter knowledge leads to this phenomenon.…”
Section: Teaching Experiencementioning
confidence: 94%
“…The results of the study detailing professional development showed a good effect on PCK. For instance, professional development programs (Ekmekci et al, 2019;Hidayat & Setyawan, 2020;Maboya et al, 2022;Sarkim, 2020), content-focused professional development (Richter et al, 2021), model/ professional training/ teacher training/ collaboration programs (Gambini & Lenart, 2021;Jeschke et al, 2021;Kurt-Birel et al, 2020;Manderfeld & Siller, 2019;Saputra et al, 2019;Sunzuma & Maharaj, 2019;Tang, 2018;Yildiz & Akyuz, 2019;Yilmaz & Demir, 2021), seminar/ workshops/ in-service training (Ansah et al, 2020;Chang et al, 2020;Kurt-Birel et al, 2020;Moh' d et al, 2021), educational course/ pedagogy course (Lau, 2019;Lee et al, 2018), school based continuous professional development/ on-site professional training (lesson study) (Helmbold et al, 2021;Mhakure, 2019), structured interventions/ professional learning workshops (Hilton & Hilton, 2018), regular meetings (Taylan et al, 2022), microteaching course/ microteaching/ teaching practicums (Setyaningrum et al, 2018) and a two-week summer institute (Schoen et al, 2019) were implemented to enhance mathematics teachers' PCK level effectively. Notably, terms such as model, professional training, teacher training and collaboration program were frequently used to represent professional development in most of the studies.…”
Section: Professional Developmentmentioning
confidence: 99%
See 1 more Smart Citation